2007
DOI: 10.1107/s0909049507045438
|View full text |Cite
|
Sign up to set email alerts
|

Relics in medieval altarpieces? Combining X-ray tomographic, laminographic and phase-contrast imaging to visualize thin organic objects in paintings

Abstract: X-ray radiography is a common tool in the study of old master paintings. Transmission imaging can visualize hidden paint layers as well as the structure of the panel or canvas. In some medieval altarpieces, relics seem to have been imbedded in the wooden carrier of paintings. These are most probably thin organic fibrous materials such as paper or textile, which in traditional radiography are shadowed by the more absorbing surrounding material. This paper studies the application potential of synchrotron-based t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 15 publications
0
30
0
1
Order By: Relevance
“…To accommodate the three-dimensional (3D) characteristics of impact damage and to study particle toughening micromechanisms, micro-focus computed tomography (µCT) [10] and synchrotron radiation computed laminography (SRCL) [11] using propagation-based phase contrast [12,13] have been used in this study. The combination of SRCL and laboratory µCT imaging methods allow the effects of particle toughening to be observed at microscopic and mesoscopic levels at routinely achievable voxel resolutions with each of the two imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To accommodate the three-dimensional (3D) characteristics of impact damage and to study particle toughening micromechanisms, micro-focus computed tomography (µCT) [10] and synchrotron radiation computed laminography (SRCL) [11] using propagation-based phase contrast [12,13] have been used in this study. The combination of SRCL and laboratory µCT imaging methods allow the effects of particle toughening to be observed at microscopic and mesoscopic levels at routinely achievable voxel resolutions with each of the two imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Typically specimens are cut to form 'matchsticks' with cross-sections of a few mm 2 [19,24] to achieve the best quality scans, but this is destructive and introduces the likelihood of cutting artefacts distorting the observed damage. SRCL, a technique better suited to laterally extended geometries [12,25] including sheet or panel like material specimens [26,27], offers non-destructive, µm-scale imaging of damage micromechanisms at local regions, without machining the specimen to a reduced cross-section [26,28]. Unlike traditional, higher resolution methods such as cross-sectional microscopy, the non-destructive nature of SRCL ensures that damage post-impact is unaffected by cutting artefacts, polishing, etc.…”
Section: Introductionmentioning
confidence: 99%
“…CXL makes use of a rotation around an axis that is not perpendicular to the radiation source/detector axis but that is tilted relative to it ( Figure 1E). By performing experiments on mock-up paintings, Krug et al [30] demonstrated that voids and hidden compartments inside paintings can be inspected in a non-destructive manner via this technique. Figure 4 illustrates how CXL allows high-resolution imaging of the local sub-surface microstructure in paintings in a non-invasive and non-destructive way.…”
Section: Computed X-ray Laminography (Cxl)mentioning
confidence: 99%
“…Originally it has been motivated by and developed for non-destructive microsystem device inspection [2,3]. Recently, the technique has been extended to applications in materials science [4,5], paleontology [6] and cultural heritage [7]. Nowadays by exploiting the high degree of coherence of the synchrotron beam, applications of SRCL have been further broadened by their combination with phasecontrast imaging methods and microscopy techniques [8,9,10].…”
Section: Introductionmentioning
confidence: 99%